Okomi plays in the leaves. [#3] - Dorman, Helen; Dorman, Clive; Hutchings, Tony; Jane Goodall Institute ([Nevada City, Calif.] : Dawn Publications ; Silver Spring, MD : In association with the Jane Goodall Institute, 2003)
On a walk with his Mama Du, Okomi, a young chimpanzee, is fascinated by falling leaves and has fun playing with them. Based on Jane Goodall's observations of chimpanzee behavior, with information about the endangered status of the animals.
3.4
K-3
Keywords: Chimpanzees -- Fiction; Animals -- Infancy -- Fiction; Chimpanzees -- Fiction; Animal babies -- Fiction